Potential application value of pigment epithelium-derived factor in sensorineural hearing loss - Sun, Zihui; Li, Xiaoguang; Li, Guangfei; Xu, Ying; Meng, Jie; Meng, Wei; He, Shuangba (Frontiers in Neuroscience, 2023)
The inner ear is a complex and precise auditory perception system responsible for receiving and converting sound signals into neural signals, enabling us to perceive and understand sound. However, the occurrence and development of inner ear diseases and auditory disorders, such as sensorineural hearing loss, remain a global problem. In recent years, there has been increasing research on the treatment of inner ear diseases and auditory regeneration. Among these treatments, pigment epithelium-derived factor (PEDF), as a multifunctional secretory protein, exhibits diverse biological activities and functions through various mechanisms, and has shown potential applications in the inner ear. This minireview comprehensively evaluates the performance of PEDF in sensorineural hearing loss in inner ear and its potential targets and therapeutic prospects.